2020
DOI: 10.1200/jco.2020.38.6_suppl.33
|View full text |Cite
|
Sign up to set email alerts
|

Real-world analysis of prostate-specific antigen (PSA) outcomes among patients with metastatic castration-resistant prostate cancer (mCRPC) treated with enzalutamide (ENZA).

Abstract: 33 Background: ENZA showed efficacy in chemotherapy-naïve men with mCRPC in a clinical trial setting (PREVAIL). We report real-world outcomes with ENZA for this population in a urology practice setting. Methods: This retrospective cohort study included men with prostate cancer newly initiating ENZA in the IntrinsiQ Specialty Solutions™ urology electronic medical records database between September 1, 2014 and February 28, 2018. Due to the approved indication in the study time frame, prescription of ENZA (first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Specifically, the OS with enzalutamide was about 30 months with or without prior chemotherapy, which is similar to results from AFFIRM and PREVAIL. PSA responses for enzalutamide seen in our study appear to be similar to other retrospective trials mentioned above (9,10). Patients receiving abiraterone however appeared to have a much poorer survival outcome; only 15 months and 7 months for no chemotherapy and prior chemotherapy respectively.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Specifically, the OS with enzalutamide was about 30 months with or without prior chemotherapy, which is similar to results from AFFIRM and PREVAIL. PSA responses for enzalutamide seen in our study appear to be similar to other retrospective trials mentioned above (9,10). Patients receiving abiraterone however appeared to have a much poorer survival outcome; only 15 months and 7 months for no chemotherapy and prior chemotherapy respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, in a real world retrospective study conducted in the United Kingdom ( 9), a greater PSA50 (defined as the percentage of patients who had a PSA decline of at least 50% from baseline) was seen in the enzalutamide group compared to abiraterone group (58% versus 31% p<0.0005), but there was no significant median OS difference between the groups (enzalutamide 13.8 months versus abiraterone 12.5 months p=0.065). Responses on enzalutamide were further supported by a retrospective cohort study (10), that showed a PSA50 of 55% in 931 men with mCRPC on enzalutamide therapy. A meta-analysis (11) demonstrated superiority of enzalutamide over abiraterone in terms of radiographic PFS, time until PSA progression, and PSA response rate in both the pre-and post-docetaxel settings, but again OS did not differ significantly between the two drugs.…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, recently reported real‐world data relating to ENZ demonstrated lower PSA50 response rates in chemotherapy‐naïve patients compared to the PREVAIL study. 19 Furthermore, another European real‐world study demonstrated a lower PFS in those receiving AA of 10.8 months, likely related to the older age, higher rates of comorbidities and visceral metastases within their cohort compared to the COU‐AA‐302 study. 20 …”
Section: Discussionmentioning
confidence: 96%
“…Similarly, recently reported real-world data relating to ENZ demonstrated lower PSA50 response rates in chemotherapy-naïve patients compared to the PREVAIL study. 19 Furthermore, another…”
Section: Discussionmentioning
confidence: 99%